EFEKTIFITAS DAN KONTRIBUSI PENERIMAAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN (IMB) TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) KOTA BAUBAU - Rais R, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the effectiveness and contribution of building permit levy (IMB) receipts to baubau city local revenue receipts. The data collection methods used are field research and library research. The method of data analysis is descriptive research. Based on the results of the effectiveness analysis, it can be concluded that the level of Realization Effectiveness for Building Permit Retribution (IMB) in Baubau City from 2016 to 2018 is in the Very Effective category with an average effectiveness level of 126.08%. In 2016 as a whole it has an effectiveness level of 110.03%. Whereas in 2017 as a whole it has an average effectiveness rate of 129.72% and in 2018 as a whole it has an average effectiveness rate of 117.71%. Based on the results of the contribution analysis that has been carried out, it appears that the Contribution of the Realization of the Building Permit Retribution (IMB) to the Regional Original Revenue of Baubau City from 2016 to 2018 is in the Very Less category with an average contribution rate to Regional Original Revenue of 2.55%. In 2016, the overall contribution reached 2.04%. Meanwhile, in 2017 as a whole, the regional original income contribution rate reached an average of 3.42%. Whereas in 2018 as a whole it has an average Regional Original Revenue contribution rate of 2.20%.